A cupric ion triggered DNA diode based on a tandem linkage–cleavage reaction. Issue 84 (4th October 2016) - Cao, Ting; Nie, Ji; Cai, Liang-Yuan; Zhang, Xiao-Hui; Zhang, De-Wen; Zhou, Ying-Lin; Zhang, Xin-Xiang
Abstract : A novel DNA functional element, a DNA diode, was developed based on a tandem linkage–cleavage process consisting of click chemistry and DNAzyme. Abstract : Based on click chemistry and DNAzyme, we constructed for the first time a cupric ion triggered DNA diode using a tandem linkage–cleavage process, which could occur in order in a programmable and autonomous manner. This DNA diode is a new DNA functional element and can precisely control the translation direction of information.